Improvement of beef cattle through breeding methods - Smith, W.H.; Akinokun, J.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Two inbred lines of purebred Shorthorn cattle were established and progressively developed, to study production traits and effects of inbreeding. Inbreeding was initiated in the Wernace Premier Line in 1949 and in the Mercury line in 1952. Both lines have remained closed to outside breeding since. Inbreeding has progressively increased as the result of successive generations of half sibbing.
Keywords: Beef; Inbreeding; Average daily gain